2022
DOI: 10.1177/11782218221111840
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity in Opioid Substitution Therapy: A Systematic Review of Interventional and Observational Studies

Abstract: Background: Use of physical activity in the treatment and follow-up of people receiving opioid substitution therapy is an understudied area of research. Therefore, the objective of this systematic review was to synthesize the currently available research on the role of physical activity in opioid substitution therapy and proper adaptions for the group. Methods: A systematic search was performed on PsycINFO, EMBASE, MEDLINE, CINAHL, and Web of Science until September 2021 (PROSPERO-reg.no: CRD42020109873). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
(275 reference statements)
0
9
0
Order By: Relevance
“…Physical activity is widely used as adjunctive therapy for people with SUD, both therapeutically and to improve health [ 10 , 31 ]. However, there are still gaps in the literature concerning how to best implement physical activity in OAT clinics, particularly in terms of adapting interventions and ensuring good adherence [ 16 ]. From our findings, most participants had experienced a decline in health and daily function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity is widely used as adjunctive therapy for people with SUD, both therapeutically and to improve health [ 10 , 31 ]. However, there are still gaps in the literature concerning how to best implement physical activity in OAT clinics, particularly in terms of adapting interventions and ensuring good adherence [ 16 ]. From our findings, most participants had experienced a decline in health and daily function.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, exercise-related interventions within this population have proven to be challenging with low adherence rates and some individuals having negative experiences to exercise [ 13 15 ]. Further, there is limited research on how to best implement exercise interventions among people receiving OAT [ 16 18 ]. A recently published systematic review identified only six intervention studies on physical activity and exercise among people in OAT [ 16 ], most of which had methodological shortcomings and were not sufficiently sized to evaluate the effects [ 19 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates a need for lifestyle interventions to reduce metabolic risk. A systematic review of physical activity among persons receiving OAT concluded that regular physical activity improved physical fitness, mental health, and substance use [ 48 ]. Robust studies on the efficacy of dietary interventions for persons with SUD are lacking, but a review of five studies indicates that interventions may improve dietary outcomes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robust studies on the efficacy of dietary interventions for persons with SUD are lacking, but a review of five studies indicates that interventions may improve dietary outcomes [ 49 ]. Most included studies reported low adherence, often due to health-related issues, homelessness, lack of transportation and lack of follow-up [ 48 , 49 ]. The frequency of obesity is lower in our sample compared to a cohort recruited from the Norwegian general population in which one-quarter of the participants were obese [ 50 ].…”
Section: Discussionmentioning
confidence: 99%